Factors Influencing Competitive Advantage: Market Orientation and Innovation - Afif Maulana Ibrahim; Hapzi Ali (Siber International Journal of Sport Education, 2023)
Competitive advantage is the main goal for companies that want to continue to exist and develop in a competitive market. Two important factors that influence the achievement of competitive advantage are market orientation and innovation. Market orientation helps companies to understand customer needs and respond to market dynamics, while innovation plays a role in creating unique new products and services. This article presents a literature review on the influence of market orientation and innovation on competitive advantage. The results of this study are: (1) Market orientation has a significant influence on competitive advantage. (2) Innovation has a significant influence on competitive advantage. (3) Market orientation and innovation have a simultaneous influence on competitive advantage.